2022
DOI: 10.1115/1.4054150
|View full text |Cite
|
Sign up to set email alerts
|

Different Phases in Manual Materials Handling Have Different Performance Criteria: Evidence From Multi-Objective Optimization

Abstract: A manual material handling task involves the phases of reaching, lifting, unloading, and standing up (RLUS). Understanding the mechanisms of manual material handling is important for occupational health and the development of assist devices. Predictive models are becoming popular in exploring which performance criterion is appropriate in the lifting phase. However, limited attempts have been performed on the other phases. The associated performance criterion for predicting other phases is unknown. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Mimicking the same mechanism can help to reduce prediction errors. Xiang et al 29 and Zheng et al 107 demonstrated that combination of dynamic-effort and stability objective functions generated more accurate simulation results than the single objective optimization. In a study, 30 it was found that the MOO approach reduced 18.9% prediction errors than a single-objective optimization for lifting motion prediction.…”
Section: Model and Motion Prediction Errorsmentioning
confidence: 99%
“…Mimicking the same mechanism can help to reduce prediction errors. Xiang et al 29 and Zheng et al 107 demonstrated that combination of dynamic-effort and stability objective functions generated more accurate simulation results than the single objective optimization. In a study, 30 it was found that the MOO approach reduced 18.9% prediction errors than a single-objective optimization for lifting motion prediction.…”
Section: Model and Motion Prediction Errorsmentioning
confidence: 99%